Obesity-Associated Nonalcoholic Fatty Liver Disease - YILMAZ, YUSUF (W B SAUNDERS CO-ELSEVIER INC, 2014)
Obesity is strongly associated with the prevalence of nonalcoholic fatty liver disease (NAFLD) in adult and pediatric populations. Nutrition, physical activity, and behavioral modifications are critical components of the treatment regimen for all obese patients with NAFLD. Bariatric surgeries that affect or restrict the flow of food through the gastrointestinal tract may improve liver histology in morbidly obese patients with nonalcoholic steatohepatitis (NASH), although randomized clinical trials and quasi-randomized clinical studies are lacking. Early detection of NASH and hepatic fibrosis using noninvasive biochemical and imaging markers that may replace liver biopsy is the current challenge.
Keywords: Obesity; Nonalcoholic fatty liver disease; Epidemiology; Pathophysiology; LIFE-STYLE MODIFICATION; BODY-MASS INDEX; UNITED-STATES; METABOLIC SYNDROME; BARIATRIC SURGERY; PHYSICAL-ACTIVITY; BIOMARKER PANEL; ADIPOSE-TISSUE; RISK-FACTORS; STEATOHEPATITIS